Indonesian Music Education, Industry, and Lifestyle - Citra Aryandari (Institut Seni Indonesia Denpasar, 2023)
Purpose: This research attempts to conduct a careful study of the influence of political, social, and industrial dynamics in Indonesia, which gave birth to the forms and products of music education. Method: This study uses a multidisciplinary cultural approach as the object researched is multidimensional. In its title, there are some entities: music education, industry, and lifestyle. Results and discussion: As with music (culture) itself, music education, which incidentally is one of the main foundations for the development of music, of course, does not just exist. Various searches have successfully linked the relationship between music education and the political and social dynamics in which music develops. Implication: Likewise, the growing trend affects the form of music products in the music industry. The phenomenon of the 'Mozart effect' as one of the trends in the music education industry, its controversy, and its presence in the realm of industrial promotion have become essential references for stringing a common thread of connection with other exciting phenomena in this study.